ANALISIS KESUKSESAN SISTEM E-COMMERCE YANG BERPARTISIPASI PADA HARBOLNAS DENGAN MENGGUNAKAN MODEL DELONE & MCLEAN - Dian Pertiwi; Fajar Rina Sejati; Septyana Prasetianingrum (Universitas Pakuan, 2020)
This study aims to analyze the success of e-commerce participating in Harbolnas from a user perspective by adopting model of Delone McLean. Data were obtained through a questionnaire using cluster random sampling technique. The hypotheses were tested by path analysis and sobel test. The results show that e-commerce participating in Harbolnas 2019 can meet the success of e-commerce based on the e-commerce success model of Delone McLean. It is shown by system quality, information quality, and service quality influenced each use and user satisfaction. In addition, information quality, use, and user satisfaction directly influenced net benefits. Meanwhile, system quality and service quality do not directly influenced net benefits. Other results indicate that system quality, information quality, and service quality also influenced net benefits through mediating use and user satisfaction. The results of this study are expected to be material for consideration for companies to maximize e-commerce that has been made.